Performance Study Of Kitchen Waste Carbonizer - Shaari, Mohd Farhan (Universiti Sains Malaysia, 2019)
There are many food waste generated from canteens, restaurant, hostels and hotels. These wastes being thrown away into the rubbish bin and disposed in landfills. The transformation of the unwanted kitchen waste into a valuable carbon end product can be accomplished by the thermochemical decomposition of organic materials using kitchen waste carbonizer. The end products can be used as high grade smokeless fuel for cooking and household heating as well as fertilizer for plants. In order to do that, the moisture content and volatile matter within the waste must be eliminated. This thesis examines the fuel characteristic of kitchen waste at different reaction temperature in the reactor vessel and time being used.